Array - Pratama, Yoga Aji; Pujosusanto, Ari (LATERNE, 2021)
One of the German language learning materials taught in grade 12 is the material on trennbare Verben. The disadvantage experienced by students is that they are not able to identify trennbare verben sentences. The subjects of this study were students of SMAN 1 Surabaya which based on the results of field observations, students were always wrong in working on questions with the trennbare verben material so that it indicated that the students did not understand about the trennbare verben material. The reason for using the video 'Separable verbs in German - Super Easy German' is because the material for trennbare verben sentences is very simple, to the point, equipped with conversations and there are German and English subtitles so that it helps students not to get confused during the research or learning process. In addition, the reason for using this video itself is also to overcome the problem of the learning process of students during COVID-19 so that they are able to learn independently during the pandemic and not only learn German through the materials provided by the teacher. This research is a quantitative quasi-experimental study (quasi-experimental) with a procedural One Group Pretest Posttest Design. The result of this study is that video is able to be an option and affect student learning outcomes because the results of the Sig score. (2-tailed) 0.000 which indicates that h0 is rejected and ha is accepted with the N-Gain test of 0.322 classified as having an impact on the medium level